E-Commerce Application Development for HNI Products Sales using the Agile Method - Syahputri, Namira; Padli Nasution, Muhammad Irwan (Sistemasi: Jurnal Sistem Informasi, 2024)
In everyday life people cannot be separated from the Internet. One of the most widely viewed aspects of Internet use is the online sales site used to sell and buy everything from small to large items. E-commerce is an electronic platform with a particular trait or characteristic. Customers always want the easiest way to order or buy, so it needs to develop an e-commerce system, which focuses on individual business transactions via the Internet (technology-based digital) using electronic applications, transactions become faster and more intense. The HNI is health and beauty companies. The HNI itself still USES its own manual to process the buying and selling of products but with the development of technology and changes in consumer behavior, the HNI views the need to expand its businesses through the development of e-commerce based web. For that to be built e-commerce web-based at HNI using the agile method to be more effective and efficient. The agile method is selected because it is flexible to adapt to changes of business needs and enables the developer to adapt quickly.